Financial Inclusion as a Mediator of Financial Literacy, Technology Adoption, and Government Policy on MSME Performance - Zaki Nur Hamam; Wida Purwidianti; Naelati Tubastuvi; Ika Yustina Rahmawati (Airlangga Journal of Innovation Management, 2026)
This study focuses on analyzing the effects of financial literacy, technology adoption, and government policies in influencing Micro, Small, and Medium Enterprises (MSMEs) in Banyumas, with financial inclusion acting as a mediator. This study utilizes a quantitative method through a convenience sampling approach, gathering data from a sample of 200 MSME stakeholders. Data has been processed using Structural Equation Modelling-Pooled Least Squares (SEM-PLS) via SmartPLS Software Version 3.0. The results show a significant positive effect of financial literacy, technology adoption, and government policies on financial inclusion. Financial literacy and technology adoption have a direct positive effect; in contrast, government policies have an insignificant direct effect, although a positive influence, on MSME performance. Financial inclusion has a surprisingly negative effect on MSME performance. However, financial inclusion still has a role as a mediator in MSMEs relating to performance among all financial literacy, technology adoption, and government policies. The observations from this paper provide an implication that financial inclusion plays a crucial role in determining business performance results. In practice, this paper supports promoting adaptive financial literacy, growth in technology adoption in financial services, and the development of policies tailored in accordance with local MSMEs. This study also enriches the literature by confirming the variation in the direction and strength of the relationship between variables in the context of developing countries, especially in non-metropolitan areas.